The possibility of culture : pleasure and moral development in Kant's aesthetics - Murray, Bradley, 1980- (Chichester, West Sussex, UK ; Malden, MA : Wiley, 2015)
The Possibility of Culture: Pleasure and Moral Development in Kant's Aesthetics presents an in-depth exploration and deconstruction of Kant's depiction of the ways in which aesthetic pursuits can promote personal moral development. Presents an in-depth exploration of the connection between Kant's aesthetics and his views on moral development Reveals the links between Kant's aesthetics and his anthropology and moral psychology Explores Kant's notion of genius and his views on the connections between the social aspects of taste and moral development Addresses aspects of Kant's ethical theor.
A Beautiful Soul -- to Which No Connoisseur or Art Collector Can Lay ClaimA Contingency of Form; Through Which Nature Gives the Rule to Art; 5 Sublimity and Esteem; Not to Disavow the Moral Self-Esteem of Such a Being; A Might of the Mind; By a Certain Subreption; 6 Choosing Culture Over Happiness; The Ultimate End of Nature; The Liberation of the Will; By the Constitution of Our Understanding; 7 Conclusion; Bibliography; Index; End User License Agreement
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Kant, Immanuel, -- 1724-1804.; Kant, Immanuel, -- 1724-1804.; Aesthetics; Ethics; PHILOSOPHY / History & Surveys / Modern; Aesthetics; Ethics; Aesthetics; Ethics; Kant, Immanuel, 1724-1804.; Electronic books; Electronic books